AMPK: Potential Therapeutic Target for Vascular Calcification - Lu, Yi; Yuan, Tan; Min, Xinjia; Yuan, Zhen; Cai, Zhejun (Frontiers in Cardiovascular Medicine, 2021)
Vascular calcification (VC) is an urgent worldwide health issue with no available medical treatment. It is an active cell-driven process by osteogenic differentiation of vascular cells with complex mechanisms. The AMP-activated protein kinase (AMPK) serves as the master sensor of cellular energy status. Accumulating evidence reveals the vital role of AMPK in VC progression. AMPK is involved in VC in various ways, including inhibiting runt-related transcription factor 2 signaling pathways, triggering autophagy, attenuating endoplasmic reticulum stress and dynamic-related protein 1-mediated mitochondrial fission, and activating endothelial nitric oxide synthase. AMPK activators, like metformin, are associated with reduced calcification deposits in certain groups of patients, indicating that AMPK is a potential therapeutic target for VC.